Polyester films and film laminates

The introduction of a polyester film with an A layer composed of aromatic polyester resin and polyamide resin addresses the challenges of insufficient piercing strength and chemical resistance in laminated packaging materials for lithium batteries, achieving enhanced film properties and reduced manufacturing complexity.

JP7661813B2Active Publication Date: 2025-04-15MITSUBISHI CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021114993
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-12
Publication Date
2025-04-15
Estimated Expiration
2041-07-12

AI Technical Summary

Technical Problem

Existing laminated packaging materials for lithium batteries in electric vehicles and hybrid vehicles face challenges with insufficient piercing strength, chemical resistance, and difficulty in thinning films, which can lead to reduced battery functionality and increased production costs.

Method used

A polyester film with a specific structure containing an A layer made of aromatic polyester resin and polyamide resin, with a piercing strength per unit thickness of 400 N/mm or more, and optionally including a carbodiimide compound as a compatibility agent, to enhance film properties.

Benefits of technology

The polyester film achieves excellent piercing resistance and is expected to have chemical resistance, allowing for further thinning of films and reducing the number of manufacturing steps, thereby improving battery safety and productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661813000001
    Figure 0007661813000001
Patent Text Reader

Abstract

To provide a polyester film which has excellent piercing resistance, can be expected to have chemical resistance, enables further thin film formation, and can contribute to reduction in the number of manufacturing processes.SOLUTION: A polyester film has a layer A containing an aromatic polyester resin (X) and a polyamide resin (Y), and has a piercing strength per unit thickness of 400 N / mm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film and a film laminate. [Background technology]

[0002] TECHNICAL FIELD Polyester films, particularly polyethylene terephthalate films and polyethylene naphthalate films, have been used in the past for a variety of applications, such as packaging, electronic components, electrical insulation, metal lamination, display components such as flexible displays, touch panels, anti-reflection, and shatter-proofing of glass, due to their excellent mechanical properties, heat resistance, and chemical resistance.

[0003] In recent years, as batteries for electric vehicles, hybrid vehicles, and other vehicles have become more powerful, there has been an increasing demand for laminated packaging materials to be made thinner and lighter as packaging materials for on-board lithium batteries. In the laminate packaging material, a biaxially oriented nylon film is generally used from the viewpoints of formability and pinhole resistance.

[0004] However, there is a risk that the nylon film itself will dissolve due to the strong acidity of the contents (such as hydrogen fluoride (HF)). In particular, batteries used in electric vehicles, hybrid vehicles, etc. have tens to hundreds of battery cells arranged in series. In such cases, if even one battery cell leaks and dissolves the nylon layers on the surfaces of the other battery cells, this could reduce the functionality of the entire battery or result in poor production yields.

[0005] Therefore, from the viewpoint of safety and productivity, it is common to laminate an acid-resistant layer such as a polyester film on the outer layer of the nylon film. As a method for producing a laminated packaging material having such an acid-resistant layer, a method has been proposed in which a polyester layer such as a polyethylene terephthalate film is laminated to a polyamide layer such as a nylon film via an adhesive layer (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2010 / 047354 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the laminate packaging material described in Patent Document 1, unless each layer has a certain thickness, the desired performance may not be exhibited. Furthermore, in the laminate packaging material, the puncture strength of the polyester film on the outer layer side is insufficient, and there are cases in which both puncture resistance and chemical resistance are insufficient. Furthermore, since different materials are laminated, it may be difficult to make the film thin or the number of manufacturing steps may increase.

[0008] The present invention has been made in consideration of the above-mentioned situation, and the problem to be solved by the present invention is to provide a novel polyester film that has excellent puncture resistance and is also expected to have chemical resistance, can be made thinner, and can contribute to reducing the number of manufacturing steps. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be easily solved by using a polyester film having a specific composition, and have completed the present invention. That is, the present invention has the following aspects.

[0010] [1] A polyester film having a layer A containing an aromatic polyester resin (X) and a polyamide resin (Y), the layer A having a puncture strength per unit thickness of 400 N / mm or more.

[0011] [2] The polyester film according to the above [1], wherein the polyamide resin (Y) contains an aromatic polyamide.

[0012] [3] The polyester film according to the above [1] or [2], wherein the content of the polyamide resin (Y) is 1 to 20 mass % based on 100 mass % of all components of the polyester film.

[0013] [4] The polyester film according to any one of the above [1] to [3], wherein the layer A further contains a compatibilizer (Z).

[0014] [5] The polyester film according to the above [4], wherein the compatibilizer (Z) comprises a carbodiimide compound.

[0015] [6] The polyester film according to the above [4] or [5], wherein the content of the compatibilizer (Z) is 1 to 10 mass % based on 100 mass % of all components of the polyester film.

[0016] [7] The polyester film according to any one of the above [1] to [6], wherein the aromatic polyester resin (X) contains polyethylene terephthalate.

[0017] [8] The polyester film according to any one of the above [1] to [7], which has a thickness of 5 to 50 μm.

[0018] [9] A packaging material for an electrochemical cell, comprising the polyester film according to any one of [1] to [8] above.

[0019]

[10] The packaging material for electrochemical cells according to the above [9], which is for exterior packaging of an in-vehicle lithium battery.

[0020]

[11] A film laminate comprising the polyester film according to any one of the above [1] to [8] and a metal layer on at least one surface of the polyester film.

[0021]

[12] The film laminate according to

[11] above, wherein the metal layer is laminated via an adhesive layer.

[0022]

[13] A packaging material for an electrochemical cell comprising the film laminate according to

[11] or

[12] above.

[0023]

[14] The packaging material for electrochemical cells according to the above

[13] , which is for exterior packaging of an in-vehicle lithium battery. Effect of the Invention

[0024] According to the present invention, there is provided a polyester film which is expected to have excellent puncture resistance and, at the same time, chemical resistance. Furthermore, the polyester film of the present invention can be made thinner, which contributes to a reduction in the number of manufacturing steps. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Next, an example of an embodiment of the present invention will be described, however, the present invention is not limited to the embodiment described below.

[0026] <<Polyester film>> The polyester film of the present invention (hereinafter also referred to as "the film") has a layer A containing an aromatic polyester resin (X) and a polyamide resin (Y), and has a puncture strength per unit thickness of 400 N / mm or more.

[0027] The present film may be a single-layer structure having only Layer A, or a multi-layer structure (i.e., a laminated film) having at least Layer A. When the present film has a multi-layer structure, it may be a two-layer structure, a three-layer structure, or a four-layer structure or more without departing from the gist of the present invention, and the number of layers is not particularly limited. However, from the viewpoint of thinning and reducing the number of manufacturing steps, a single-layer structure or a multi-layer structure of three or less layers is preferable, a single-layer structure or a multi-layer structure of three or less layers consisting of only a plurality of A layers is more preferable, and a single-layer structure is even more preferable.

[0028] When there are a plurality of layers A, the components constituting the layers A and their contents may be the same or different. Furthermore, in the case of a multi-layer structure having at least layer A, the layer A is preferably the outermost layer.

[0029] The film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred, and a biaxially stretched film is more preferred from the viewpoints of balance of mechanical properties, flatness, and thinning.

[0030] Hereinafter, as one example of the embodiment according to the present invention, a case consisting of only layer A containing aromatic polyester resin (X) and polyamide resin (Y) will be described.

[0031] <Aromatic polyester resin (X)> Layer A preferably contains an aromatic polyester resin (X) as a main component resin. Here, the aromatic polyester resin (X) refers to a polyester resin having aromatic groups in at least one of the polyvalent carboxylic acid unit and the polyhydric alcohol unit constituting the polyester. The main component resin herein means the resin that has the largest mass ratio among the resins constituting the present film, and means 50 mass % or more of the resins constituting the present film.

[0032] The aromatic polyester resin (X) may be either a homopolyester or a copolymer polyester.

[0033] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the aliphatic glycol include ethylene glycol, diethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. Representative examples of the homopolyester include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene-2,6-naphthalate (PEN). In the present invention, PET and PEN, which have excellent chemical resistance, are preferred, and PET is more preferred from the viewpoint of versatility.

[0034] On the other hand, examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc. The copolymer polyester contains an aromatic compound in the dicarboxylic acid component and / or the glycol component. When the aromatic polyester resin (X) is a copolymer polyester, it is preferably a copolymer containing 30 mol% or less of a third component, more preferably 60 mol% or more, preferably 80 mol% or more of ethylene terephthalate units or ethylene-2,6-naphthalate units, and from the viewpoint of versatility, it is even more preferably 60 mol% or more, preferably 80 mol% or more of ethylene terephthalate units.

[0035] The aromatic polyester resin (X) according to the present invention may contain one type of polyester alone or a plurality of different types of polyesters, and preferably contains PET, and more preferably contains only PET.

[0036] The polymerization catalyst for polyester is not particularly limited, and a conventionally known compound can be used, for example, titanium compounds, germanium compounds, antimony compounds, manganese compounds, aluminum compounds, magnesium compounds, calcium compounds, etc. Among these, at least one of titanium compounds and antimony compounds is preferred.

[0037] In order to suppress the amount of precipitation of oligomer components, the film may be produced using a polyester having a low content of oligomer components as the raw material. As a method for producing a polyester having a low content of oligomer components, various known methods can be used, such as a method of performing solid phase polymerization after the production of a polyester.

[0038] Particles may be contained in the aromatic polyester resin (X) mainly for the purpose of imparting lubricity and preventing scratches in each process. The type of particles is not particularly limited as long as the particles are capable of imparting lubricity, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.

[0039] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, block, rod-like, flat, etc. may be used. There is also no particular restriction on the hardness, specific gravity, color, etc. These particles may be used alone or in combination of two or more kinds, if necessary.

[0040] The average particle size of the particles used is usually preferably 5 μm or less, more preferably in the range of 0.01 to 3 μm. By having the average particle size in the above range, the present film is given an appropriate surface roughness, and good slipping properties and smoothness can be ensured.

[0041] When particles are contained, the particle content is usually preferably less than 5% by mass, and more preferably in the range of 0.0003 to 3% by mass. When the particle content is in this range, the transparency and slipperiness of the film become good.

[0042] The method of adding the particles is not particularly limited, and a conventionally known method can be adopted. For example, the particles can be added at any stage of the production of the aromatic polyester resin (X), but it is preferable to add the particles after the completion of the esterification or transesterification reaction.

[0043] In addition to the above-mentioned particles, conventionally known ultraviolet absorbents, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added as necessary.

[0044] In the present film, the content of aromatic polyester resin (X) is preferably 70 to 98% by mass, more preferably 75 to 97% by mass, and further preferably 80 to 96% by mass, based on 100% by mass of all components. If the content of aromatic polyester resin (X) is within this range, the present film is expected to also have good chemical resistance. When the present film has a single-layer structure consisting of only Layer A, the content of aromatic polyester resin (X) in the present film is equal to the content in Layer A.

[0045] When the present film is a laminated film having a multi-layer structure consisting of only a plurality of A layers, the content of the aromatic polyester resin (X) is the content in the entire present film. For example, even if the present film is a laminated film having layers each consisting of an A layer having a different content of aromatic polyester resin (X), the content of aromatic polyester resin (X) is the content of the entire laminated film. In this case, the content of aromatic polyester resin (X) in each A layer is preferably within the above range, specifically 70 to 98% by mass, more preferably 75 to 97% by mass, and even more preferably 80 to 96% by mass, based on 100% by mass of all components of A layer. In other words, it is preferable that the content of aromatic polyester resin (X) in each A layer satisfies the above range, and then satisfies the content of the entire present film.

[0046] <Polyamide resin (Y)> The A layer contains a polyamide resin (Y). The polyamide resin (Y) may be an aliphatic polyamide or an aromatic polyamide. The polyamide resin (Y) may be one type alone or two or more types in combination, or an aliphatic polyamide and an aromatic polyamide in combination, but it is preferable that the polyamide resin (Y) contains an aromatic polyamide, and more preferable that the polyamide resin (Y) is only an aromatic polyamide.

[0047] Examples of aliphatic polyamides include aliphatic nylons and their copolymers. Specific examples of the aliphatic polyamides include polycapramide (nylon-6), poly-ω-aminoheptanoic acid (nylon-7), poly-ω-aminononanoic acid (nylon-9), polyundecaneamide (nylon-11), polylauryl lactam (nylon-12), polyethylenediamineadipamide (nylon-2,6), polytetramethyleneadipamide (nylon-4,6), polyhexamethyleneadipamide (nylon-6,6), polyhexamethylenesebacamide (nylon-6,10), polyhexamethylenedodecamide (nylon-6,12), polyoctamethyleneadipamide (nylon-8,6), polydecamethyleneadipamide (nylon-10,8), caprolactam / lauryl lactam copolymer (nylon-6 / 12), caprolactam, Examples of the polyamides include caprolactam / ω-aminononanoic acid copolymer (nylon-6 / 9), caprolactam / hexamethylenediammonium adipate copolymer (nylon-6 / 6,6), lauryllactam / hexamethylenediammonium adipate copolymer (nylon-12 / 6,6), ethylenediamine adipamide / hexamethylenediammonium adipate copolymer (nylon-2,6 / 6,6), caprolactam / hexamethylenediammonium adipate / hexamethylenediammonium sebacate copolymer (nylon-6,6 / 6,10), ethyleneammonium adipate / hexamethylenediammonium adipate / hexamethylenediammonium sebacate copolymer (nylon-6 / 6,6 / 6,10), etc. Two or more of these aliphatic polyamides may be mixed.

[0048] Preferred aliphatic polyamides include nylon-6, nylon-6,6 and nylon-6 / 6,6 (a copolymer of nylon-6 and nylon-6,6).

[0049] Examples of aromatic polyamides include crystalline aromatic polyamides obtained by polycondensation reaction of aromatic diamines such as metaxylylenediamine and paraxylylenediamine with dicarboxylic acids or derivatives thereof such as adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, terephthalic acid, and isophthalic acid. Among these, crystalline aromatic polyamides such as polymetaxylene adipamide (MXD-nylon) are preferred, and specific examples include S-6007 and S-6011 (both manufactured by Mitsubishi Gas Chemical Company, Inc.).

[0050] Further, there can be mentioned non-crystalline aromatic polyamide (amorphous nylon) obtained by a polycondensation reaction between an aliphatic diamine such as hexamethylenediamine and a dicarboxylic acid or a derivative thereof such as terephthalic acid or isophthalic acid. Among these, a copolymer of hexamethylenediamine-terephthalic acid-hexamethylenediamine-isophthalic acid is preferable, and a specific example thereof is Sealer PA (manufactured by DuPont-Mitsui Polychemicals Co., Ltd.).

[0051] In the present invention, aromatic polyamides are preferred, and crystalline aromatic polyamides are more preferred.

[0052] In the total mass of all components of the present film (100 mass%), the content of polyamide resin (Y) is preferably 1 to 20 mass%, more preferably 2 to 18 mass%, and further preferably 3 to 15 mass%. When the content of polyamide resin (Y) is within this range, the present film has good puncture resistance. In addition, within this range, the content of the aromatic polyester resin (X) can be ensured, and therefore good chemical resistance can also be expected. When the present film has a single-layer structure consisting of only Layer A, the content of the polyamide resin (Y) in the present film is equal to the content in Layer A.

[0053] When the present film is a laminated film having a multi-layer structure consisting of only a plurality of A layers, the content of polyamide resin (Y) is the content in the entire present film. For example, even if the present film is a laminated film consisting of only A layers each having a different content of polyamide resin (Y), the content is the content of polyamide resin (Y) in the entire laminated film. In this case, the content of polyamide resin (Y) in each A layer is preferably within the above range, specifically 1 to 20 mass%, more preferably 2 to 18 mass%, and even more preferably 3 to 15 mass%, based on 100 mass% of all components of A layer. In other words, it is preferable that the content of polyamide resin (Y) in each A layer satisfies this range, and then satisfies the content of the present film as a whole.

[0054] <Compatibilizer (Z)> It is preferable that the layer A further contains a compatibilizer (Z). The compatibilizer (Z) can improve film formability by compatibilizing the aromatic polyester resin (X) and the polyamide resin (Y).

[0055] The compatibilizer (Z) preferably contains a carbodiimide compound. The carbodiimide compound is a compound having a carbodiimide group (-N=C=N-), and is not particularly limited as long as it has at least one carbodiimide group.

[0056] Examples of the carbodiimide compound include monocarbodiimide compounds having one carbodiimide group in the molecule, and polycarbodiimide compounds having two or more carbodiimide groups in the molecule.

[0057] Examples of the monocarbodiimide compound include aliphatic monocarbodiimides such as N,N'-diisopropylcarbodiimide, N,N'-di-tert-butylcarbodiimide, N-(3-(dimethylamino)propyl)-N'-ethylcarbodiimide, and N,N'-dicyclohexylcarbodiimide; and aromatic monocarbodiimides such as N,N'-diphenylcarbodiimide, N,N'-di-p-tolylcarbodiimide, N,N'-bis(dimethylphenyl)carbodiimide, N,N'-bis(methoxyphenyl)carbodiimide, N,N'-bis(nitrophenyl)carbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, and N,N'-bis(triphenylsilyl)carbodiimide.

[0058] Examples of the polycarbodiimide compound include aliphatic polycarbodiimides such as poly(4,4'-dicyclohexylmethanecarbodiimide); and aromatic polycarbodiimides such as poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(methylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(1,3,5-triisopropylphenylenecarbodiimide), poly(1,3,5-triisopropylphenylene-co-1,5-diisopropylphenylenecarbodiimide), and poly(4,4'-diphenylmethanecarbodiimide).

[0059] The carbodiimide compounds may be used alone or in combination of two or more. Among these, polycarbodiimide compounds are preferred, and aliphatic polycarbodiimide compounds are more preferred, and specific examples thereof include Carbodilite (registered trademark) HMV-5CA-LC (manufactured by Nisshinbo Chemical Inc.) and Carbodilite (registered trademark) LA-1 (manufactured by Nisshinbo Chemical Inc.).

[0060] When the compatibilizer (Z) is used, the content thereof is preferably from 1 to 10 mass %, more preferably from 1 to 5 mass %, and further preferably from 2 to 3 mass %, based on 100 mass % of all components of the present film. When the content of the compatibilizer (Z) is within the above range, the compatibility between the aromatic polyester resin (X) and the polyamide resin (Y) is improved, and deterioration of moldability due to a decrease in melt viscosity is suppressed, improving film formability. When the present film has a single-layer structure consisting of only Layer A, the content of the compatibilizer (Z) in the present film is equal to the content in Layer A.

[0061] When the present film is a laminated film having a multi-layer structure consisting of only a plurality of A layers, the content of the compatibilizer (Z) is the content in the entire present film. For example, even if the present film is a laminated film consisting of only A layers with different contents of the compatibilizer (Z), the content of the compatibilizer (Z) is the content of the entire laminated film. In this case, the content of the compatibilizer (Z) in each A layer is preferably within the above range, specifically 1 to 10 mass%, more preferably 1 to 5 mass%, and even more preferably 2 to 3 mass%, based on 100 mass% of all components of the A layer. In other words, it is preferable that the content of the compatibilizer (Z) in each A layer satisfies the above range, and then satisfies the content of the entire present film.

[0062] In the present invention, the compatibilizer (Z) may be preliminarily mixed with the aromatic polyester resin (X) and / or the polyamide resin (Y) and then melt-kneaded. Alternatively, the compatibilizer (Z) may be added to the molten aromatic polyester resin (X) and / or the polyamide resin (Y) and then kneaded. Alternatively, a resin compound such as a masterbatch may be prepared by any of these methods, and then melt-kneaded with the aromatic polyester resin (X) and / or the polyamide resin (Y).

[0063] <Manufacturing method of this film> Next, the method for producing the present film will be described using the case where the present film is a biaxially stretched polyester film as an example. When the present film is a biaxially stretched polyester film, it is preferable to first produce an unstretched sheet, and then stretch it in two directions to obtain a biaxially stretched polyester film.

[0064] The unstretched sheet is preferably obtained by feeding the above-mentioned aromatic polyester resin (X), polyamide resin (Y), and particles and other additives, which are blended as necessary, to an extruder, mixing them appropriately, extruding them from a die of the extruder as a molten sheet, and cooling and solidifying them on a rotating cooling drum. In this case, it is preferable to increase the adhesion between the sheet and the rotating cooling drum in order to improve the flatness of the sheet, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably adopted. When the present film has a multi-layer structure, the layers may be co-extruded by a co-extrusion method to form an unstretched sheet having a multi-layer structure.

[0065] The aromatic polyester resin (X) and polyamide resin (Y) as raw materials may be fed to an extruder as pellets or the like after being appropriately dried, and particles and other additives may be appropriately blended with the pellets. When the compatibilizer (Z) is used, it can be used as described above.

[0066] The unstretched sheet is then stretched uniaxially and then biaxially. Specifically, the unstretched sheet is first stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction. In this case, the stretching temperature is usually 70 to 170° C., and the stretch ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times.

[0067] It is preferable to subsequently perform heat treatment under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially stretched polyester film. In the above stretching, a method of performing stretching in one direction in two or more stages can be adopted. In that case, it is preferable to perform the stretching so that the final stretch ratios in both directions are each within the above range.

[0068] The present film can also be produced by a simultaneous biaxial stretching method, in which the unstretched sheet is simultaneously stretched and oriented in the longitudinal and transverse directions under a temperature controlled condition usually at 70 to 120° C., preferably 80 to 110° C., and the stretching ratio is 4 to 50 times, preferably 7 to 35 times, and more preferably 10 to 25 times in terms of area ratio. Then, it is preferable to subsequently perform a heat treatment under tension or relaxation of 30% or less at a temperature of 170 to 250° C. to obtain a stretched and oriented film. Regarding the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.

[0069] The longitudinal direction of the film refers to the direction in which the film advances during the film production process, i.e., the winding direction of the film roll. The width direction refers to the direction parallel to the film surface and perpendicular to the longitudinal direction, i.e., the direction parallel to the central axis of the roll when the film is in a roll shape.

[0070] <Physical properties of this film> The puncture strength per unit thickness of the present film is 400 N / mm or more, preferably 450 N / mm or more, more preferably 500 N / mm or more, and particularly preferably 550 N / mm or more. If it is within this range, it can be said to have good puncture resistance. The upper limit of the puncture strength per unit thickness is not particularly limited, but is usually 700 N / mm or less.

[0071] The haze of the present film is preferably 12.0% or less, more preferably 10.0% or less, further preferably 8.0% or less, and particularly preferably 6.0% or less. If it is within such a range, sufficient transparency is obtained. The lower limit is not particularly limited, but is usually 0.01% or more.

[0072] Furthermore, when the haze of the present film is 5.0% or less, preferably 4.0% or less, it can be suitably used in applications requiring transparency, such as pharmaceutical packaging.

[0073] From the viewpoints of economy, productivity, moldability, and the like, the thickness of the present film is preferably from 5 to 50 μm, more preferably from 7 to 40 μm, and further preferably from 10 to 30 μm. If the thickness is 5 μm or more, the strength of the film is sufficient and tearing or breaking during molding is unlikely to occur, whereas if the thickness is 50 μm or less, the strength of the film is appropriate, and not only does the film have good molding conformability, but also the film has good adhesion to a metal layer (e.g., an aluminum layer) when used for the exterior of an in-vehicle lithium battery. When the present film has a multi-layer structure having layers other than the layer A, the thickness of the layer A is preferably in the range of 80 to 99% of the total thickness of the present film.

[0074] <Application> Since the present film has excellent puncture resistance and is also expected to have chemical resistance, it can be suitably used as a packaging material for electrochemical cells (hereinafter also referred to as "the present packaging material") for packaging lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, capacitors, electrolytic capacitors, etc., and is particularly suitable for use as an exterior packaging for lithium batteries, particularly lithium batteries for vehicles. In this way, the present packaging material can be used by using the present packaging material as an exterior member, sandwiching an electrochemical cell between the exterior members, and sealing the periphery of the exterior members by heat fusion (heat sealing). Therefore, a suitable form of the present packaging material is a packaging material for electrochemical cells that houses an electrochemical cell and seals the electrochemical cell by heat sealing the peripheral portions, and is a packaging material for electrochemical cells that includes at least the present film.

[0075] The most preferred embodiment of the present packaging material comprises a base layer, an adhesive layer, a metal layer and a heat-sealing layer, and the present film is used as the base layer. The adhesive layer, metal layer and heat-sealing layer are not particularly limited, but the following layers are preferably used.

[0076] Furthermore, since the film has excellent puncture resistance, it can also be suitably used for pharmaceutical packaging.

[0077] <<Film laminate>> The film laminate of the present invention (hereinafter also referred to as "the laminate") preferably has a metal layer laminated on at least one side of the film. The metal layer to be laminated is not particularly limited, and examples thereof include layers formed from metals, metal oxides, complexes of metals and metal oxides, etc. The metal layer may also be laminated on a film such as a separately prepared resin film. Specifically, examples of metals include aluminum, nickel, etc., and the metal layer may also be formed using a film on which silicon oxide, alumina, etc. are vapor-deposited. Of these, aluminum is preferred because of its excellent formability and moisture resistance. The thickness of the aluminum layer is preferably 10 to 60 μm, more preferably 12 to 48 μm, and further preferably 15 to 45 μm. If the thickness is 10 μm or more, it can withstand the pressure during molding and is less likely to break. On the other hand, if the thickness is 60 μm or less, the moldability is good.

[0078] In the present laminate, in order to form a metal layer on the present film, a method in which an adhesive layer is interposed therebetween is preferred. The adhesive layer is not particularly limited, but may be a pressure sensitive adhesive, a pressure sensitive adhesive sheet, an adhesive, etc., and from the viewpoint of excellent adhesiveness, an adhesive is preferably used. As the adhesive, for example, a polyolefin adhesive, an acrylic adhesive, a polyester adhesive, an epoxy adhesive, a polyurethane adhesive, etc. may be used.

[0079] In addition, the laminate preferably has an easy-adhesion layer on at least one side of the film in order to improve adhesion to the metal layer. The easy-adhesion layer is a layer that can improve adhesion between the film and another layer, for example, a layer that improves adhesion to an adhesive layer used when laminating the film to a metal layer, and thus excellent adhesion and improved adhesive strength can be achieved. The method of providing the easy-adhesion layer is not particularly limited, but examples thereof include in-line coating and off-line coating. In-line coating is a method of coating within the polyester film production process, more specifically, a method of coating after melt extrusion of polyester and longitudinal stretching and before transverse stretching. Off-line coating is a method of providing an easy-adhesion layer using a coating device in a separate process after the polyester film is produced.

[0080] <Application> Since the laminate has excellent puncture resistance and is also expected to have chemical resistance, it can be suitably used as a packaging material for electrochemical cells (hereinafter also referred to as "the packaging material") for packaging lithium ion batteries, lithium ion polymer batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, capacitors, electrolytic capacitors, etc., and is particularly suitable for use in the exterior packaging of lithium batteries, particularly lithium batteries to be mounted on vehicles. In this way, the packaging material can be used by using the packaging material as an exterior member, sandwiching an electrochemical cell between the exterior members, and sealing the periphery of the exterior members by heat fusion (heat sealing). Therefore, a suitable form of the present packaging material is a packaging material for electrochemical cells that houses an electrochemical cell and seals the electrochemical cell by heat sealing the peripheral portions, and is a packaging material for electrochemical cells that includes at least the present film.

[0081] The present laminate preferably uses the present film as a substrate layer, and is used in the form of the present film (substrate layer) / adhesive layer / metal layer, or the present film (substrate layer) / easy-adhesion layer / adhesive layer / metal layer, etc.

[0082] The most preferred embodiment of the present packaging material is one that includes the present laminate and a heat-sealing layer. The heat-sealing layer can be formed using, for example, polypropylene, polyethylene, or the like.

[0083] <<Explanation of terms>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0084] The present invention will now be described in further detail with reference to examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.

[0085] <Evaluation method> (1) Intrinsic viscosity of polyester (dl / g) When particles were added, 1 g of polyester from which the particles had been removed was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.

[0086] (2) Puncture strength per unit thickness The puncture strength (N) was measured in accordance with JIS Z1707, and the value obtained by dividing the puncture strength (N) by the film thickness was defined as the puncture strength per unit thickness (N / mm).

[0087] (3) Film haze The measurement was performed using a haze meter DH-2000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS K7136.

[0088] <Materials used> (Aromatic polyester resin (X)) X1: homopolyethylene terephthalate (intrinsic viscosity = 0.640 dl / g) (Polyamide resin (Y)) Y1: Nylon MXD6 Grade S6007 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) (Compatibilizer (Z)) Z1: Carbodilite (registered trademark) HMV-5CA-LC (manufactured by Nisshinbo Chemical Inc.) Z2: A masterbatch (intrinsic viscosity = 0.734 dl / g) in which 10% by mass of Carbodilite (registered trademark) HMV-5CA-LC (manufactured by Nisshinbo Chemical Inc.) was blended with homopolyethylene terephthalate

[0089] Example 1 As shown in Table 1, X1, Y1 and Z1 were mixed as raw materials in a mass ratio of 87:10:3. The mixed raw materials were fed into a small twin-screw extruder, melt-extruded at 280°C, and cooled and solidified on a cooling roll set at 60°C to obtain an unstretched sheet. The unstretched sheet was then stretched at a magnification of 3.0×3.0 at 90° C. using a batch-type small biaxial stretching machine, and heated in an oven at 230° C. for 10 seconds to obtain a 35 μm biaxially stretched polyester film. The properties of the obtained polyester film were evaluated by the above-mentioned methods, and the evaluation results are shown in Table 1.

[0090] (Examples 2 to 5) A biaxially stretched polyester film was obtained in the same manner as in Example 1, except that the composition was as shown in Table 1. The evaluation results are shown in Table 1.

[0091] Comparative Example 1 A biaxially stretched polyester film was obtained in the same manner as in Example 1, except that the composition was as shown in Table 1. The evaluation results are shown in Table 1.

[0092] [Table 1]

[0093] As shown in Table 1, the polyester films of Examples 1 to 5 had improved puncture resistance due to the inclusion of Layer A in which the aromatic polyester resin (X) and the polyamide resin (Y) were blended. In addition, since the present film contains a large amount of aromatic polyester resin (X) relative to the amount of polyamide resin (Y), it is expected that the film will also have the chemical resistance that aromatic polyester resin (X) inherently has. [Industrial Applicability]

[0094] The polyester film of the present invention has excellent puncture resistance and is also expected to have chemical resistance, and therefore can be suitably used for battery exteriors, particularly for lithium battery exteriors, and particularly for vehicle-mounted lithium battery exteriors. Furthermore, when the polyester film of the present invention has excellent transparency, it can be suitably used for packaging medicines.

Claims

1. The laminate has a layer A containing an aromatic polyester resin (X) and a polyamide resin (Y), A polyester film for use as a packaging material for electrochemical cells, having a puncture strength per unit thickness of 400 N / mm or more.

2. The polyester film for use as a packaging material for electrochemical cells according to claim 1 , wherein the polyamide resin (Y) contains an aromatic polyamide.

3. 3. The polyester film for packaging materials for electrochemical cells according to claim 1, wherein the content of the polyamide resin (Y) is 1 to 20 mass%, based on 100 mass% of all components of the layer A of the polyester film.

4. The polyester film for use as a packaging material for electrochemical cells according to any one of claims 1 to 3, wherein the layer A further contains a compatibilizer (Z).

5. The polyester film for use as a packaging material for electrochemical cells according to claim 4 , wherein the compatibilizer (Z) comprises a carbodiimide compound.

6. 6. The polyester film for packaging materials for electrochemical cells according to claim 4 or 5, wherein the content of the compatibilizer (Z) is 1 to 10 mass% based on 100 mass% of all components of the A layer of the polyester film.

7. The polyester film for packaging materials for electrochemical cells according to any one of claims 1 to 6, wherein the aromatic polyester resin (X) contains polyethylene terephthalate.

8. The polyester film for packaging electrochemical cells according to any one of claims 1 to 7, having a thickness of 5 to 50 µm.

9. A packaging material for electrochemical cells, comprising the polyester film for electrochemical cell packaging according to any one of claims 1 to 8.

10. The packaging material for electrochemical cells according to claim 9, which is for exterior packaging of lithium batteries to be mounted on vehicles.

11. A film laminate comprising the polyester film for use as a packaging material for electrochemical cells according to any one of claims 1 to 8 and a metal layer on at least one surface of the polyester film.

12. The film laminate according to claim 11 , wherein the metal layer is laminated via an adhesive layer.

13. A layer A containing an aromatic polyester resin (X) and a polyamide resin (Y), A film laminate having a metal layer on at least one side of a polyester film having a puncture strength per unit thickness of 400 N / mm or more, A film laminate, wherein the metal layer is laminated via an adhesive layer.

14. A packaging material for an electrochemical cell, comprising the film laminate according to any one of claims 11 to 13.

15. The packaging material for electrochemical cells according to claim 14, which is for exterior packaging of lithium batteries to be mounted on vehicles.

Citation Information

Patent Citations

  • Biaxially oriented film and container

    JP2000034357A

  • Polyester resin composition and molded article

    JP2003113295A

  • Polyester resin composition and molded form

    JP2004285194A

  • Polyester resin composition

    JP2007084642A

  • Polyester resin composition, oriented film / sheet consisting of the same and packaging material using the same

    JP2007126596A